2019
DOI: 10.1017/s1047951119002920
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous closure of muscular ventricular septal defect by growth of right ventricular muscle bundles: a rare mechanism

Abstract: AbstractWe present a case of an 18-year-old male with large anterior muscular ventricular septal defect. Assessment by echocardiography showed that the defect has completely closed by the growth of muscle bundles that formed a pouch-like structure on the right ventricular side. This unusual mechanism of closure has been reported in one prior case report. In our report, we present images obtained by three-dimensional echocardiography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Several previous studies have revealed that muscular and perimembranous VSDs could be closed spontaneously depending on the site of the defect. It has been hypothesized that an aneurysm of the membranous septum and leaflet of the tricuspid valve was the most responsible for the closure in perimembranous VSD 6,7 . Although VSD in the mentioned patient was not spontaneously closed, it seems that the membranous portion of the interventricular septum had abnormally elongated up to RV‐free wall with a defect at that site resulting in this abnormality (VSD).…”
Section: Discussionmentioning
confidence: 89%
“…Several previous studies have revealed that muscular and perimembranous VSDs could be closed spontaneously depending on the site of the defect. It has been hypothesized that an aneurysm of the membranous septum and leaflet of the tricuspid valve was the most responsible for the closure in perimembranous VSD 6,7 . Although VSD in the mentioned patient was not spontaneously closed, it seems that the membranous portion of the interventricular septum had abnormally elongated up to RV‐free wall with a defect at that site resulting in this abnormality (VSD).…”
Section: Discussionmentioning
confidence: 89%